FUZZY MODELING OF HETEROGENEOUS KNOWLEDGE IN INTELLECTUAL EDUCATIONAL SYSTEMS - Yury A. Kravchenko; Victoriya V. Bova (Открытое образование (Москва), 2016)
The article is devoted to development of formalized representation model for intellectual educational systems knowledge base definition in an uncertain conditions. Such modeling will enable at the design stage of the information knowledge management system to avoid errors of experts in determining the evaluation criterion of competence, the options of individual training trajectories, requirements for the types and number of knowledge representation forms and test tasks.